2006
DOI: 10.1111/j.1467-9353.2006.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mandatory Price Reporting Requirements on Level, Variability, and Elasticity Parameter Estimations for Retail Beef Prices

Abstract: Moving to scanner based and quantity-weighted monthly average retail beef price series has changed the price series significantly. Quantity-weighted price levels are lower and more volatile. Perhaps most important, calculated elasticities for the quantity-weighted averages are lower than for the historical simple average data. Elasticity estimates for simple average monthly price data are also larger than for weekly data, raising the possibility that historic demand analyses have significantly overstated own p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…There is evidence mandatory price reporting that includes retail meat scanner data can improve retail meat price reporting (e.g., Lensing and Purcell 2006). The importance of this result appears to need emphasis.…”
Section: Policy and Research Implications And Concluding Remarksmentioning
confidence: 89%
See 1 more Smart Citation
“…There is evidence mandatory price reporting that includes retail meat scanner data can improve retail meat price reporting (e.g., Lensing and Purcell 2006). The importance of this result appears to need emphasis.…”
Section: Policy and Research Implications And Concluding Remarksmentioning
confidence: 89%
“…Lensing and Purcell (2006) compared the well-known retail meat prices reported by the Bureau of Labor Statistics (BLS) with scanner-based prices, which included price featuring by retailers, that resulted from the mandatory price reporting mandate. Lensing and Purcell found that quantity-weighted, monthly average retail prices for five of six beef items were lower than BLS prices.…”
Section: Evaluative Research Since Mandatory Price Reportingmentioning
confidence: 99%
“…Research by Lensing and Purcell (2006) shows that historic retail prices as collected by BLS are in fact too high. Our efforts show, as producer groups often assert, that the BLS prices do not always respond to price declines at the wholesale level.…”
Section: Discussionmentioning
confidence: 99%
“…Scanner data allow significant advances in understanding food product marketing because they enable estimation of firm‐, brand‐, and commodity‐level demand models (Cotterill, 1994; Capps and Love, 2002). Lensing and Purcell (2006) find that the prices collected by the Bureau of Labor Statistics (BLS) have been higher than the prices that consumers use to make their buying decisions. Volume weighted prices, provided by scanner data, more accurately reflect what consumers actually pay for fresh meat in contrast to BLS summaries of posted prices (Lensing and Purcell, 2006).…”
Section: Datamentioning
confidence: 98%